Insights into the assembly and activation of the microtubule nucleator γ-TuRC - Liu, Peng; Župa, Erik; Neuner, Annett; Böhler, Anna; Flemming, Dirk; Ruppert, Thomas; Pfeffer, Stefan; Schiebel, Elmar (Nature, 2020)
Here, we present the cryo-EM structure of γ-TuRC from Xenopus laevis at 4.8 Å global resolution, revealing a 14-spoked arrangement of GCPs and γ-tubulins in a partially flexible open left-handed spiral with a uniform sequence of GCP variants (Fig. 1a). Via specific interactions with other GCP proteins, the GCP6-specific insertion domain scaffolds the assembly of the γ-TuRC. Unexpectedly, we identified Actin as a bona fide structural component of γ-TuRC with functional relevance in MT nucleation. The γ-TuRC spiral geometry is suboptimal for MT nucleation and a controlled conformational rearrangement of the γ-TuRC is required for its activation. Collectively, our cryo-EM reconstruction provides unprecedented insights into the molecular organization, the assembly and the activation mechanism of vertebrate γ-TuRC and will serve as an important framework for the mechanistic understanding of fundamental biological processes associated with MT nucleation, e.g. meiotic and mitotic spindle formation and centriole biogensis4.
Published online: 19 December 2019
Das PDF enthält zusätzlich einen Anhang von 26 Seiten
Gesehen am 21.02.2020